Shakespeare & Hathaway : private investigators. Season one [videorecording (DVD)] - Joyner, Jo, 1977-; Benton, Mark, 1965-; McBride, Patrick Walshe (BBC, 2019)
A ten part detective series from the BBC about an oddball couple of private detectives named Luella Shakespeare and Frank Hathaway. Investigating crime in Stratford-upon-Avon, the duo quickly discover all is not as peaceful as it seems in this little theatre town.